Expansão Sucroalcooleira no Bioma Cerrado: Tendências, cenários e impactos. - RIBEIRO, Noely Vicente (2010)
Due to the shortage of fossil fuels, as well as due to the current environmental issues related to the emission of greenhouse gases, there has been a growing demand for alternative, renewable and sustainable, energy sources. In particular, biofuels, such as ethanol, are becoming more proeminent each day. In Brazil, considered the largest ethanol producer and exporter in the world, such demand has triggered a fast growing (and insufficiently planned) sugarcane expansion, mostly in the Cerrado biome. Within this scope, and relying on an exploratory analysis of the characteristics and patterns of the sugarcane distribution in the Cerrado, this research aimed at understanding the underlying mechanisms and physiographic constraints behind the ongoing expansion. Assuming this expansion will be preferentially over cultivated pastures, for both economic and environmental reasons, we propose a territorial ordainment based on spatial analysis and according to major landscape attributes (i.e. relief, land-use, soil type, available infrastructure) and environmental laws. In addition, through the use of a dynamic modeling approach, accounting for both the current expansion trends, as well as the occurrence of favorable areas, we generated a sugarcane scenario up to 2035. Our main results include: a) in the Cerrado, sugarcane is highly dependent on the available infrastructure, flat terrains and mechanizable oxisols; b) sugarcane expansion is occurring at the expenses of other crop commodities; c) the proposed territorial ordainment will enable an expansion almost sixfold the current sugarcane area, without compromising other crops, the environment, or the remnant vegetation areas; d) as opposed, and kept the current trends, the scenario derived from the dynamic modeling shows that new sugarcane may take up to 45% of the agricultural areas in the Cerrado, reducing crop diversity and seriously impacting some of the biome watersheds. In spite the fact that both scenarios yield approximate the same expansion, the area on which they occur will be quite different. In fact, the so-called ―constrained‖ scenario is likely to have less impacts on the environment and food production. Overall, our results suggest that through territorial ordainment, a substantial increase in ethanol production, in harmony with the environment and other economic activities, is possible to occur.